The role of antitissue transglutaminase assay for the diagnosis and monitoring of coeliac disease: a French–Italian multicentre study. Issue 5 (1st May 2003) - Tonutti, E; Visentini, D; Bizzaro, N; Caradonna, M; Cerni, L; Villalta, D; Tozzoli, R
Abstract : Aims: Tissue transglutaminase (tTG) was recently identified as the major autoantigen in coeliac disease. The aim of this multicentre study was to evaluate the impact of a new immunoenzymatic assay for the detection of IgA anti-tGT antibodies. Methods: Seventy four Italian and French clinical laboratories participated in this study; anti-tTG IgA with an enzyme linked immunosorbent assay (ELISA) method using guinea pig liver extract as the coating antigen, anti-endomysium IgA autoantibodies (EMA), and total serum IgA were determined in 7948 patients, 1162 of whom had coeliac disease (737 untreated cases and 425 on a gluten free diet). A proportion of the sera were then sent to a reference laboratory for anti-tTG retesting with an ELISA method using recombinant human tTG antigen. Results: Seven thousand four hundred and fifty eight (93.8%) sera were EMA/antiguinea pig tTG concordant (positive or negative); 490 (6.2%) were non-concordant. The sensitivity of EMA and antiguinea pig tTG in the 737 untreated patients with coeliac disease was 92.1% and 94.8%, respectively, and the specificity was 99.8% and 99.2%, respectively. Retesting of the discordant sera showed that of the 162 sera classified as EMA negative/antiguinea pig tTG positive, only 49 were positive for human recombinant anti-tTG, and that 39 of these were also EMA positive. Furthermore, of the 36 sera classified as EMA positive/antiguinea pig tTG negative, only two were confirmed as EMA positive. Conclusions: The antiguinea pig tTG assay is more sensitive but less specific than EMA, whereas the antihuman recombinant tTG assay is far more specific and just as sensitive as antiguinea pig tTG. Testing for EMA presents considerable interpretative problems and is difficult to standardise.